Exceptional heat island intensities also occur in medium-sized cities - Amorim, Margarete Cristiane de Costa Trindade [UNESP]; Dubreuil, Vincent; Teixeira, Danielle Cardozo Frasca [UNESP]; Amorim, Amanda Trindade [UNESP]; Brabant, Charlotte (Elsevier, 2024)
The escalation of extreme heat exposure, resulting from both climate change and the urban heat island (UHI) effect, poses a significant threat not only to major urban centers but also to medium-sized cities. This research had three primary objectives: a) to conduct a temporal analysis of the occurrence and frequency of UHI with strong magnitudes in medium-sized cities situated in tropical and temperate climates; b) to conduct a spatial analysis by examining representative episodes of robust UHI within in medium-sized cities; and c) to establish relationships between nocturnal air and surface temperatures when UHI reach their maximum intensities. The cities under examination are Presidente Prudente, Brazil (located in a tropical climate), and Rennes, France (in a temperate climate). The analysis was carried out at both temporal and spatial scales. Temporally, we computed average monthly hourly temperatures for representative locations in both urban and rural areas of both cities, spanning the period from 2017 to 2022. This approach takes into consideration the variability in seasonal and synoptic conditions. By investigating the hourly evolution of the UHI and analyzing monthly averages of its intensities throughout a 24-h cycle, we identified extraordinary episodes. An episode was defined for both the tropical and temperate environments of each city, reflecting their unique characteristics and facilitating intraurban spatial analysis. To compare nocturnal air and surface temperatures, we utilized remote sensing data and air temperature recordings in the two cities. The results showed that medium-sized cities, located in diverse climatic zones, may also encounter situations characterized by extreme UHI, with temperature increases exceeding 6 °C. Such occurrences are more prevalent in tropical environments than in temperate ones. These often-overlooked scenarios, which have received limited attention in the existing literature and have been inadequately considered in governmental policies, underscore the lack of preparedness in communities to address such phenomena. With the expansion and densification of urban areas and the increasing impact of global climate change, leading to more frequent heatwaves, these discomforting thermal scenarios, well-documented contributors to heightened urban mortality, may become increasingly pressing concerns for medium-sized cities in the foreseeable future.
Keywords: Medium-sized cities; Presidente Prudente/Brazil; Rennes/France; Urban heat island of strong magnitude